Leadership and influence: Evidence from an artefactual field experiment on local public good provision - Giovanna D'Adda (University of Zurich, Department of Economics, 2011)
This paper studies the effect of leadership on the level and evolution of pro-social behavior using an artefactual field experiment on local public good provision. Participants decide how much to contribute to an actual conservation project. They can then revise their donations after being randomly matched in pairs on the basis of their authority and having observed each other's contributions. Authority is measured through a social ranking exercise identifying formal and moral leaders within the community. I find that giving by a pair is higher and shows a lower tendency to decrease over time when a leader is part of a pair. This is because higher-ranked pair members in general, and leaders in particular, donate more and are less likely to revise contributions downwards after giving more than their counterparts. Leadership effects are stronger when moral authority is made salient within the experiment, in line with the ethical nature of the decision under study. These findings highlight the importance of identifying different forms of leadership and targeting the relevant leaders in projects aimed at local public good provision.
Keywords: D7; H4; O1; 330; Leadership; Local public goods; Experimental; Colombia; Lokale öffentliche Güter; Allokation; Soziales Verhalten; Kolumbien; Test